2018
DOI: 10.1371/journal.pone.0194759
|View full text |Cite
|
Sign up to set email alerts
|

Glucose sensor-augmented continuous subcutaneous insulin infusion in patients with diabetic gastroparesis: An open-label pilot prospective study

Abstract: Erratic blood glucose levels can be a cause and consequence of delayed gastric emptying in patients with diabetes. It is unknown if better glycemic control increases risks of hypoglycemia or improves hemoglobin A1c levels and gastrointestinal symptoms in diabetic gastroparesis. This study investigated the safety and potential efficacy of continuous subcutaneous insulin infusion (CSII) and continuous glucose monitoring (CGM) in poorly controlled diabetes with gastroparesis. Forty-five type 1 or 2 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 37 publications
1
19
0
1
Order By: Relevance
“…The use of an insulin pump is another option for individuals with type 1 diabetes and insulin-requiring type 2 diabetes with gastroparesis (330). A small but positive 12-month trial reported a 1.8% reduction in A1C and decreased hospitalizations with insulin pump use (331).…”
Section: Consensus Recommendationsmentioning
confidence: 99%
“…The use of an insulin pump is another option for individuals with type 1 diabetes and insulin-requiring type 2 diabetes with gastroparesis (330). A small but positive 12-month trial reported a 1.8% reduction in A1C and decreased hospitalizations with insulin pump use (331).…”
Section: Consensus Recommendationsmentioning
confidence: 99%
“…DGp may be an indication for insulin-pump therapy (CSII) in patients with type 1 diabetes mellitus [ 101 ]. A recent National Institute of Diabetes and Digestive and Kidney Diseases (NIDDK) Gastroparesis Consortium (GpCRC)-funded open labeled pilot study of 42 diabetics with DGp (both types 1 and 2) showed improved glycemic control, less hypoglycemia and an improved DGP symptom score with the use of sensor-augmented pump or CSII and CGM) [ 102 ].
Fig.
…”
Section: Management Of Diabetic Gastroparesismentioning
confidence: 99%
“…Since the consortium began recruitment, more than 1000 gastroparesis patients have been enrolled in longitudinal databases and three major prospective studies enrolling more than 100 patients each have been conducted . Longitudinal demographic and clinical data relating to age, sex, symptom duration, traumatic events preceding symptom onset such as early adverse life events, both physiological and psychological, comorbid illnesses, associated psychological dysfunction, disease‐specific quality of life, healthcare resource utilization (including hospitalizations and emergency department visits), and prior and ongoing treatments have been systematically collected in all enrolled patients. In addition to organizing clinical data, establishing a biobank with collection of specimens in a central repository will greatly facilitate translational research that will contribute to our understanding of the underlying pathophysiology.…”
Section: Future Research Directions In Cvsmentioning
confidence: 99%
“…Since the consortium began recruitment, more than 1000 gastroparesis patients have been enrolled in longitudinal databases and three major prospective studies enrolling more than 100 patients each have been conducted 49,55,56. Longitudinal demographic and clinical data relating to age, sex, symptom duration,48,56,57 traumatic events preceding symptom onset such as early adverse life events, both physiologi-This will enable us to identify novel biomarkers to make an accurate diagnosis and predict response to therapies. Examples of such models which have been highly successful include both organic disorders such as inflammatory bowel disease58 and functional GI disorders such as gastroparesis.…”
mentioning
confidence: 99%